Agressões por arma de fogo: um problema de saúde pública - Bianca Santana Dutra (2014)
The violence has set up one of the main causes of morbidity and mortality worldwide and in Brazil, which has reached epidemic proportions, threatening the development of peoples and affects the quality of life. This study aims to evaluate the magnitude and severity of violence as a result of injuries by Gun (PAF). The project was approved by the Research Ethics Committee (COEP) of the Federal University of Minas Gerais (UFMG) Opinion on the Evaluation and Assessment Ethics Certificate (CAAE) No 02235212.2.0000.5149). For this were developed two (02) studies: Article 01: Victims of aggression by firearms assisted by the Mobile Emergency Care Service of a municipality in the state of Minas Gerais, Article 02: mortality profile analysis in Brazil for aggression firearm, 2001 to 2011. The first study aimed to characterize the profile of the victims in derivations of aggression by firearms assisted by the Mobile Emergency Service (EMS) in Sete Lagoas and region for the period 2010 to 2013, treatment is a cross-sectional study was conducted chi-square test and multiple correspondence analysis (ANACOR). The results represent the universe of 288 PAF calls. Of the 288 events, most of the victims were male 253 (87.8%) were over 20 years old 177 (61.5%). Most calls were puncture wounds, gunshot 236 (81.9%) in the city of Sete Lagoas 274 (95.1%) held in 202 days (70.1%), bailed on the type ambulances USA 151 (52.4%), with less than seven minutes to perform the service 165 (57.3%), and taken to the hospital 179 (62.2%). Regarding the location of the lesion, 93 (32.3%) were in head / neck, 97 (33.7%) in the trunk and 49 (17.0%) in upper and lower limbs. The second study aimed to analyze the mortality profile of aggression by firearms in Brazil between 2001 and 2011, it is a descriptive study using population-based data, was conducted descriptive analysis. The results represent the universe of 1,452,415 deaths from external causes in Brazil from 2001 to 2011, of which 417 808 were caused by firearms. Increases progressively up the number of fatal victims of aggression by firearms, with the sociodemographic profile of these basically represented by very young men, single, of black (or brown color), with the highest level of schooling primary education (in most often incomplete) that are affected in the street. Given the impact of the high number of deaths by firearm pointing a serious public health problem with social, cultural and economic interface emerges the need for convergence of efforts and synergy of actions to create coping strategies of this phenomenon with due complexity that is required. It follows is essential to identify and characterize the PAF victim population in order to develop educational strategies to prevent and control diseases not only by the health sector, but also public safety, seeking the face of violence.